2020
DOI: 10.1088/1758-5090/ab7e76
|View full text |Cite
|
Sign up to set email alerts
|

Directly coaxial 3D bioprinting of large-scale vascularized tissue constructs

Abstract: Three-dimensional (3D) bioprinting of soft large-scale tissues in vitro is still a big challenge due to two limitations, (i) the lack of an effective way to print fine nutrient delivery channels (NDCs) inside the cell-laden structures above the millimetre level; (ii) the need for a feasible strategy to vascularize NDCs. Here, a novel 3D bioprinting method is reported to directly print cell-laden structures with effectively vascularized NDCs. Bioinks with desired tissue cells and endothelial cells (ECs) are sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 40 publications
0
108
0
Order By: Relevance
“…Coaxial printing can also aid angiogenesis. Printing of cell-laden sheath and sacrificial or crosslinking core has also been shown to promote vessel-like arrangement and expression of endothelial-specific biomarkers [ 45 , 46 , 62 , 63 ]. Self-arranged lumen structures also emerge from cell migration through homogenous cell-laden core material [ 22 , 28 ] ( Fig.…”
Section: Applications Of Coaxial Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Coaxial printing can also aid angiogenesis. Printing of cell-laden sheath and sacrificial or crosslinking core has also been shown to promote vessel-like arrangement and expression of endothelial-specific biomarkers [ 45 , 46 , 62 , 63 ]. Self-arranged lumen structures also emerge from cell migration through homogenous cell-laden core material [ 22 , 28 ] ( Fig.…”
Section: Applications Of Coaxial Printingmentioning
confidence: 99%
“…Additionally, nutrient exchange within constructs is a formidable barrier. While coaxial bioprinting of vasculature has demonstrated its ability to enable thicker tissue fabrication, these tissues still have relatively small volumes (usually all dimensions are under a centimeter), and future studies will need to continue to push this limit [ 63 ]. Time of fabrication for thick tissues is another key barrier that must be critically addressed, especially for sensitive cells [ 127 ].…”
Section: Future Perspectivementioning
confidence: 99%
“…[ 88 ] The filamentous structures, thus, formed can be used for nerve tissue. [ 89 ] Large amounts of fiber can form a film or coating. The scaffold formed by the oriented structure of the filament can also manipulate the cell behavior.…”
Section: How To Achieve 3d Cell Culture?mentioning
confidence: 99%
“…Several research papers exploited this technique [ 27 29 ], and Jia et al showed good endothelialization of the hollow channels and a 21-days cell culture under perfusion [ 30 ]. More recently, Shao et al obtained thicker vascularized constructs – up to 1 cm – and were able to combine three coaxial nozzles to yield multicellular tissue matrices [ 31 ]. While the main drawback of coaxial bioprinting is in creating bifurcations, it also shares a hurdle with the other extrusion printing techniques in creating hierarchical networks, since vessels are usually created by a single extrusion of filament.…”
Section: Extrusion Bioprinting: Coaxial Nozzlesmentioning
confidence: 99%